Peran Hedging Decision dalam Memoderasi Free-Cash-Flow, Leverage dan Liquidity terhadap Nilai Perusahaan - Indriyani MS, Eka; Herdiana (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
The food and beverage industry an important sector in the Indonesian economy as it contributes to consumption, economic growth, and employment. However, value fluctuations remain a challenge, with a decline in 2020, a recovery in 2021-2022, and another weakening in 2023 due to economic instability and declining industrial activity. This suggests that the value of companies in this sector is heavily influenced by external factors. This study uses a quantitative approach with multiple regression, based on the financial statements of 21 food and beverage companies on the IDX in 2019-2024. The sample was selected purposively and analyzed using SPSS. The results of the study show that free cash flow has a positive and significant effect on the company's value. Then, hedging decisions do not have a significant influence on moderating the influence of liquidity and company value. These findings have important implications for company management to manage financial strategies and risks more effectively to increase the company's value in a competitive market. Keywords: Free Cash Flow, Leverage, Liquidity, Nilai Perusahaan